2008
DOI: 10.1259/dmfr/73393014
|View full text |Cite
|
Sign up to set email alerts
|

Primary tuberculous osteomyelitis of the mandible: a case report

Abstract: A 10-year-old female child presented with a gradually increasing swelling of 2 months' duration on the left side of her face. The history given by the guardian was not very specific. However, the history revealed possible contact between the child and a tuberculous patient. The initial clinical and radiological evaluation indicated either a chronic residual dentoalveolar abscess, tuberculosis (TB) of the mandible or a malignancy. Routine laboratory investigations were grossly unremarkable with only the erythro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 11 publications
1
17
0
6
Order By: Relevance
“…4,5 TB should be considered in the differential diagnosis of chronic joint disease 4 even if routine investigations for TB are negative. 5 A study by Lanka et al 6 on the role of fine needle aspiration cytology of lymph nodes in the diagnosis of cutaneous TB states that the fine needle aspiration cytology smears in their patients with cutaneous TB with lymphadenitis were negative for AFB by the ZiehlNeelsen stain, while varying degrees of positivity are reported by others. It was concluded that an absence of AFB in smears showing an otherwise characteristic cytological picture should not weigh against the diagnosis of TB.…”
Section: Discussionmentioning
confidence: 97%
“…4,5 TB should be considered in the differential diagnosis of chronic joint disease 4 even if routine investigations for TB are negative. 5 A study by Lanka et al 6 on the role of fine needle aspiration cytology of lymph nodes in the diagnosis of cutaneous TB states that the fine needle aspiration cytology smears in their patients with cutaneous TB with lymphadenitis were negative for AFB by the ZiehlNeelsen stain, while varying degrees of positivity are reported by others. It was concluded that an absence of AFB in smears showing an otherwise characteristic cytological picture should not weigh against the diagnosis of TB.…”
Section: Discussionmentioning
confidence: 97%
“…It may occur through a carious tooth or in an area of gingivitis. [21][22][23] Secondary infection to the maxillofacial region can occur by haematogenous spread of the bacilli from a primary focus elsewhere in the body. 24 In the present study no information was available regarding TB status, so it cannot be excluded as a possible aetiology.…”
Section: Discussionmentioning
confidence: 99%
“…A regional extension of the soft tissue lesion may involve the underlying bone. However, involvement of the mandible by tuberculous infection is extremely rare as it contains less cancellous bone [9]. In the secondary type, oral tuberculosis coexists with the pulmonary disorder.…”
Section: Discussionmentioning
confidence: 99%